02 FLUKTUASI HARGA CABAI MERAH BESAR DI PASAR SENTRAL MAROS (Studi Kasus di Pasar Sentral Maros, Kecamatan Turikale Kabupaten Maros) - Jurnal Agribis; Rismawati Rismawati; Mohammad Anwar Sadat; Abd. Asis Pata (Universitas Muslim Maros, 2021)
The learning objectives to be achieved in this study are to know how the price fluctuation of large red chilies in the central market of Maros and to know what factors influence the price fluctuation of big red chili in the central market of Maros. So that we can get knowledge and solve every problem that exists in the central market of Maros, especially price fluctuations. Data were collected from the survey results using a questionnaire and supplemented with observations, observations and field documentation. The data that has been collected is then processed to obtain real data which is used for analysis purposes. Data were obtained from questionnaires which were then processed and analyzed using multiple regression analysis techniques with the SPSS version 16.0 program. This analysis includes: classical assumption test, multiple regression analysis, hypothesis testing through t test and F test, and analysis of the coefficient of determination (R2). The results showed that the development of the price of large red chilies, has an increasing trend every month from April to June because it is influenced by several factors, namely religious events, unpredictable weather and the increase in the price of fuel oil (BBM). The highest price of red chili is IDR 30,000 / kg in May and June, on the third and fourth weeks and the lowest price is IDR 17,000 / kg in April, on the fourth week. The highest average price of large red chilies occurred in June, namely Rp. 26,500 and the lowest occurred in April, namely Rp. 18,500.